2015
DOI: 10.1103/physrevd.91.063519
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic microwave background anisotropies in the timescape cosmology

Abstract: We analyze the spectrum of cosmic microwave background (CMB) anisotropies in the timescape cosmology: a potentially viable alternative to homogeneous isotropic cosmologies without dark energy. We exploit the fact that the timescape cosmology is extremely close to the standard cosmology at early epochs to adapt existing numerical codes to produce CMB anisotropy spectra, and to match these as closely as possible to the timescape expansion history. A variety of matching methods are studied and compared. We perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 78 publications
(207 reference statements)
1
26
0
Order By: Relevance
“…Assuming that timescape cosmology is a valid description of the Universe, the (bare, in the language of timescape cosmology) Hubble parameter for dense environment is expected to be 50.1 ± 1.7 km s −1 Mpc −1 and the average (from inside a wall) observed (dressed, in the language of timescape cosmology) Hubble parameter to be 61.7 ± 3.0 km s −1 Mpc −1 (Duley et al 2013) based on the at that time current Planck results (Planck Collaboration et al 2014a,b). Very similar values were found earlier by Wiltshire (2007);Leith et al (2008) according to the best fit on supernovae Type Ia (Riess et al 2007), cosmic microwave background (CMB) (Bennett et al 2003;Spergel et al 2007) and Baryonic acoustic oscillations (Cole et al 2005;Eisenstein et al 2005) data and later by Nazer & Wiltshire (2015), albeit with larger error bars. Adopting those values, timescape cosmology can reproduce the observed accelerated expansion without having to introduce dark energy.…”
Section: Concept Of the Cosmological Testsupporting
confidence: 87%
See 1 more Smart Citation
“…Assuming that timescape cosmology is a valid description of the Universe, the (bare, in the language of timescape cosmology) Hubble parameter for dense environment is expected to be 50.1 ± 1.7 km s −1 Mpc −1 and the average (from inside a wall) observed (dressed, in the language of timescape cosmology) Hubble parameter to be 61.7 ± 3.0 km s −1 Mpc −1 (Duley et al 2013) based on the at that time current Planck results (Planck Collaboration et al 2014a,b). Very similar values were found earlier by Wiltshire (2007);Leith et al (2008) according to the best fit on supernovae Type Ia (Riess et al 2007), cosmic microwave background (CMB) (Bennett et al 2003;Spergel et al 2007) and Baryonic acoustic oscillations (Cole et al 2005;Eisenstein et al 2005) data and later by Nazer & Wiltshire (2015), albeit with larger error bars. Adopting those values, timescape cosmology can reproduce the observed accelerated expansion without having to introduce dark energy.…”
Section: Concept Of the Cosmological Testsupporting
confidence: 87%
“…Several tests for timescape cosmology were proposed in Wiltshire (2010Wiltshire ( , 2012Wiltshire ( , 2014, most of which are rather complex. So far, they have not been able to produce striking evidence neither for nor against timescape cosmology, and timescape cosmology remains within the uncertainties of current observational data (Smale & Wiltshire 2011;Duley et al 2013;Sapone et al 2014;Nazer & Wiltshire 2015;Dam et al 2017).…”
Section: Introductionmentioning
confidence: 97%
“…pec_expan-bbl tions of emerging average negative curvature models, include, e.g., toy models of collapsing and expanding spheres (Räsänen 2006) or Lemaître-Tolman-Bondi (LTB) regions (Nambu & Tanimoto 2005;Kai et al 2007), a peak model (Räsänen 2008), a metric template model (Larena et al 2009;Chiesa et al 2014), bi-scale or more general multi-scale models (Wiegand & Buchert 2010;Buchert & Räsänen 2012), the Timescape model (Wiltshire 2009;Duley, Nazer, & Wiltshire 2013;Nazer & Wiltshire 2015), the virialisation approximation (Roukema, Ostrowski, & Buchert 2013), an effective viscous pressure approach , and Swiss cheese models that paste exact inhomogeneous solutions into holes in a homogeneous (FLRW) background (Bolejko & Célérier 2010; the Tardis model of Lavinto, Räsänen, & Szybka 2013). Updates to many of these models should benefit from an observationally justified estimate of H bg 1 .…”
Section: Introductionmentioning
confidence: 99%
“…What is particularly interesting for the coming decade are predictions for redshift evolution of Ω k , the average curvature parameter, from telescopes such as Euclid. Majerotto showed that statistically homogeneous and isotropic general-relativistic cosmological models in which the expansion rate history is observationally realistic, including the Timescape 40,99,100 and Tardis 45 models, have Ω k (z) relations that should be observationally distinguishable from ΛCDM to high significance by Euclid.…”
mentioning
confidence: 99%